A New Mouse Avatar Model of Non-Small Cell Lung Cancer - Russo, Maria Veronica; Faversani, Alice; Gatti, Stefano; Ricca, Dario; Del Gobbo, Alessandro; Ferrero, Stefano; Palleschi, Alessandro; Vaira, Valentina; Bosari, Silvano (Frontiers in Oncology, 2015)
Introduction Lung cancer remains the leading cause of tumor-related deaths, despite advances in the understanding of the disease pathogenesis and in its clinical treatment. It is crucial to develop novel technologies to discover disease biomarkers and predict individual therapy response. Materials and Methods We established 48 Patients-Derived Tumor Xenografts (PDTXs) implanted in the subrenal capsule of immunodeficient mice using thin, precision-cut tumor tissue slices, derived from 5 patients affected by Non Small Cell Lung Cancer. Twenty-six tissue slices were immediately processed and implanted at sample recovery (dPDTX), whereas the remaining sections were cultured on specific organotypic supports at 37°C and 5% CO2 for 24h before grafting (cPDTX). At sacrifice, xenografts tissue morphology, proliferation (Ki67) and histotype markers were analyzed. Oncogenic miRNAs profiles were assessed in PDTXs, human tumors and serum from one patient. Results Xenografts retained the original cancer features and there were no differences between dPDTXs and cPDTXs. Squamous Cell Carcinoma (SCC) xenografts showed a higher engraftment rate than Adenocarcinoma (AC) derived tumors. At basal time, Ki67 levels were higher in SCCs than in ACs, and the expression levels of genes associated to a stem cell-like phenotype were also more expressed in SCC samples. The analysis of oncogenic miRNAs showed that circulating miR-19b, -21 and -210 levels were correlated with higher Ki67 expression in xenografts. Conclusion Our study implemented the PDTX model with thin, precision-cut tumor slices from small tumors, which could be useful for clinical applications and predictive purposes. The different engraftment success is likely determined by tumor histotype, high proliferation index and the expression of genes essential for cancer stem cells maintenance. Our PDTXs model could be a valid tool to expand primary tumors for the discovery of new biomarkers and explore therapeutic options.